2010
DOI: 10.1007/s10493-010-9343-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological control of broad mites (Polyphagotarsonemus latus) with the generalist predator Amblyseius swirskii

Abstract: The broad mite is a serious pest of a variety of crops worldwide. Several phytoseiid mites have been described to control these mites. However, broad mites are still one of the major pest problems on greenhouse pepper in South-eastern Spain. The generalist predatory mite A. swirskii is widely used against other pests of pepper plants such as thrips and whiteflies, the latter being a vector of broad mites. We assessed the potential of A. swirskii to control broad mites. The oviposition rate of A. swirskii on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 16 publications
1
35
0
1
Order By: Relevance
“…The reduced photosynthetic activity in leaves due to severe mite infestation also causes flower and fruit shedding which in turn reduces the number of fruits formed and yield [10]. The findings further confirmed that yellow mites attack the young leaves and shoots, causing significant losses, especially the stoppage of growth or atrophy of the branches and the flower drop markedly as reported earlier by many workers resulting in a fewer number of fruits formed in the plants [11].…”
Section: Effect Of Polyphagotarsonemus Latus Infestation On Chilli Frsupporting
confidence: 76%
“…The reduced photosynthetic activity in leaves due to severe mite infestation also causes flower and fruit shedding which in turn reduces the number of fruits formed and yield [10]. The findings further confirmed that yellow mites attack the young leaves and shoots, causing significant losses, especially the stoppage of growth or atrophy of the branches and the flower drop markedly as reported earlier by many workers resulting in a fewer number of fruits formed in the plants [11].…”
Section: Effect Of Polyphagotarsonemus Latus Infestation On Chilli Frsupporting
confidence: 76%
“…Amblyseius swirskii can feed on various types of food including arthropod prey but also plant materials like pollen and honeydew (Momen and El-Saway 1993). Previous studies showed that A. swirskii can successfully develop and reproduce on a wide range of food sources such as whiteflies (Nomikou et al 2001;Calvo et al 2008;Messelink et al 2008), thrips (Arthurs et al 2009;Chow et al 2010), eriophyid mites (El-Laithy 1998;Park et al 2010), broad mites (van Maanen et al 2010;Onzo et al 2012), spider mites (Xu and Enkegaard 2010) and plant pollen (Kutuk and Yigit 2011;Park et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoseiid mites are important natural enemies in many agricultural systems (Helle and Sabelis 1986;de Moraes and Flechtmann 2008 (Peña and Osborne 1996;Weintraub et al 2003;Jovicich et al 2009;van Maanen et al 2010;Sarmento et al 2011;Rodríguez-Cruz 2014). Of those, A. herbicolus is frequently found in association with chilli pepper plants infested with broad mites in Minas Gerais (Matos 2006;Rodríguez-Cruz 2014).…”
Section: Introductionmentioning
confidence: 99%